Review of “Children” by Irena Popović (Belgrade, National Theatre, 2022) (Sound Stage Screen, 2023)
Review of Children, an opera in seventeen songs, with music by Irena Popović, based on the novel by Milena Marković.Belgrade, National Theatre, October 8, 2022.